UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN BAHASA INDONESIA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE CO-OP CO-OP PADA SISWA KELAS XII.IPA-1 SMA N 1 TALAMAU - Iriani Iriani (JURNAL MANAJEMEN PENDIDIKAN, 2017)
ABSTRACTBased on the results of students learning Class XII.1SMA N 1 Talamau in the subjects of Bahasa Indonesia found that the results of student learning in the Indonesian language is still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about Efforts to Increase student learning outcomes in the subjects of Bahasa Indonesia Conclude the contents of drama through the reading of drama text through Co-op Co-op Model in Class XII.IPA-1 SMA N 1 Talamau District Western Pasaman. This study is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 23 students of Class XII.IPA-1 SMA N 1 Talamau. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been proposed, it can be concluded that Co-op Co-op cooperative learning model can improve student learning outcomes in the Indonesian language. Summing up the content of drama through reading drama text in SMA N 1 Talamau. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 61.87 (Enough) increased to 89.17 (Good) with an increase of 27.30%.Keywords: Learning Outcomes, Bahasa Indonesia, Co-op Co-op Model